2020
DOI: 10.1074/jbc.ra119.012280
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycans on EGF domain-specific O-GlcNAc transferase (EOGT) facilitate EOGT maturation and peripheral endoplasmic reticulum localization

Abstract: Epidermal growth factor (EGF) domain-specific O-GlcNAc transferase (EOGT) is an endoplasmic reticulum (ER)-resident protein that modifies EGF repeats of Notch receptors and thereby regulates Delta-like ligand-mediated Notch signaling. Several EOGT mutations that may affect putative N-glycosylation consensus sites are recorded in the cancer database, but the presence and function of N-glycans in EOGT have not yet been characterized. Here, we identified N-glycosylation sites in mouse EOGT and elucidated their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Then, cells were counter-stained with DAPI (Southern Biotech, Birmingham, AL, USA). All the slides were examined by TiEA1R Confocal Microscopy with NIS Elements (Nikon, Japan) [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, cells were counter-stained with DAPI (Southern Biotech, Birmingham, AL, USA). All the slides were examined by TiEA1R Confocal Microscopy with NIS Elements (Nikon, Japan) [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The antibodies used were anti-Lewis X antibody Comprehensive O-GlcNAc glycoproteomics on NOTCH1 EGF repeats reported a comprehensive analysis of whole O-Glc and O-Fuc sites in the same mouse NOTCH1 expressed in HEK293T cells (28,29). In particular, our study showed that the 16 EGF domains (EGF2, 4,10,12,13,14,16,19,20,21,25,27,28,31,33) with putative O-Glc sites were O-glucosylated, except for EGF9 (28).…”
Section: Hybrid Quadrupole Ft Linear Ion Trap Ms Analysis -mentioning
confidence: 74%
“…Plasmid constructs -Expression vectors for NOTCH1 EGF repeats (pSectag2C/mNotch1-EGF1-36:MycHis-IRES-EGFP), EOGT (pSectag2C/EOGT), and dEGF20 ΔGlcΔFuc (pSectag2C/dEGF20 ΔGlcΔFuc :MycHis-IRES-EGFP) have been previously reported (18,23). Expression vectors for NOTCH1 EGF24-28 repeats (pSectag2C/mNotch1-EGF [24][25][26][27][28]:MycHis) have been reported…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations